Legal Analysis of the Death Penalty for Drug Traffickers from the Perspective of Human Rights - Wulandari, Siska; Setiyanegara, Ery (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2025)
This study analyzes the application of the death penalty for drug traffickers in Indonesia from the perspective of Human Rights (HR). The research employs a qualitative approach, utilizing document analysis and interviews with legal experts, human rights activists, and policymakers to gather comprehensive insights into the implications of the death penalty. The findings indicate that although the death penalty is viewed as a stringent measure to combat drug-related crimes, its implementation often contradicts the principles of human rights guaranteed by the 1945 Constitution and international instruments. This research identifies the discrepancies between the death penalty policy and humanitarian values, highlighting that the death penalty has not proven effective in reducing drug crime rates. Furthermore, this study recommends policy reforms that focus more on rehabilitation and the protection of human rights. The results of this research are expected to contribute to the development of more humane and effective legal policies in addressing drug-related issues in Indonesia.